Manajemen Komunikasi dalam Pembelajaran Studi Kasus Pola Komunikasi Guru dan Siswa Di TK Asy-Syarifah: Communication Management in Learning Case Study of Teacher and Student Communication Patterns in Asy-Syarifah Kindergarten - siregar, Irma Suryani (JURNAL TILA ( Tarbiyah Islamiyah Lil Athfaal ), 2023)
Abstract Communication is very important in the learning process. If teachers are less able to communicate effectively with their students, the material will not be conveyed properly. Therefore, in carrying out the learning process required good communication. In this research, it will be discussed how teacher and student communication techniques in the learning process, factors supporting teacher and student communication in learning and factors inhibiting teacher and student communication in learning. This type of research is qualitative research. The data sources consist of primary and secondary data sources. The data collection technique consists of interviews, observation and documentation then analyzed in three stages, namely data reduction, data presentation and drawing conclusions. The results of the study show that (1) teacher and student communication techniques in learning at Asy-Syarifah Kindergarten are a) persuasive techniques, namely communication techniques in the form of persuasion by giving gifts, b) informative communication techniques, namely providing clear information about the tasks to be carried out by students, c) instructional/coercive communication techniques, namely giving educative sanctions to students who violate them. (2) The supporting factors for teacher and student communication in learning at Asy-Syarifah Kindergarten are that the communicator (the person who conveys the message) must be intelligent and authoritative, the communicant (the person who receives the message) must be intelligent and concentrated, and the message conveyed must be interesting. (3) The inhibiting factors for teacher and student communication in the learning process at Asy-Syarifah Kindergarten are channel disturbances and sematic disturbances.